Inhibition of endoplasmic reticulum stress alleviates cigarette smoke-induced airway inflammation and emphysema - Wang, Yong (Oncotarget, 2017)
Chronic bronchitis and emphysema are pathologic features of chronic obstructive pulmonary disease (COPD). Cigarette smoke (CS)-induced endoplasmic reticulum (ER) stress has been implicated in the COPD development, but the molecular mechanism by which it contributes to COPD etiology and the specific role it plays in COPD pathogenesis remain poorly understood. Here, we aimed to determine the role of ER stress in the pathogenesis of CS-induced airway inflammation and emphysema. Exposure to CS significantly increased the expression of ER stress markers in Beas-2B cells and in mouse lungs, possibly through the production of oxidative stress. Further, inhibition of ER stress by 4-phenylbutyric acid (4-PBA) reduced CS extract-induced inflammation in Beas-2B cells through the modulation of NF-κB signaling. 4-PBA also protected against CS-induced airway inflammation and the development of emphysema in mice, which was associated with a reduction in NF-κB activation and alveolar cell apoptosis in the lungs. Taken together, our results suggest that ER stress is crucial for CS-induced inflammation and emphysema, and that targeting ER stress may represent a novel approach to the treatment of COPD.